2020
DOI: 10.1101/2020.01.29.925974
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A Systematic Evaluation of Single-cell RNA-sequencing Imputation Methods

Abstract: 6The rapid development of single-cell RNA-sequencing (scRNA-seq) technology, with increased sparsity compared to bulk RNA-sequencing (RNA-seq), has led to the emergence of many methods for preprocessing, including imputation methods. Here, we systematically evaluate the performance of 18 state-of-the-art scRNA-seq imputation methods using cell line and tissue data measured across experimental protocols. Specifically, we assess the similarity of imputed cell profiles to bulk samples as well as investigate wheth… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
85
2

Year Published

2020
2020
2021
2021

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 60 publications
(90 citation statements)
references
References 61 publications
3
85
2
Order By: Relevance
“…A previous systematic comparison [18] instead found that the use of SAVERX for denoising data and scran for clustering yielded better performance on the ability to recover differentially expressed genes, whereas we focused on the ability to recover cell populations. Another disagreement with the present recommendations come from the study of Hou et al [10] that recommends SAVERX and discourage the use of DCA for better clustering, whereas our study found opposite results for these tools. Several differences in the design of our study could explain this contrast, such as the use of different metrics (ARI at true number of clusters, mean precision/ recall), of different datasets (Koh, Kumar, simMix simulations) and the use of different filtering and normalization strategies.…”
Section: Limitations and Open Questionscontrasting
confidence: 99%
See 2 more Smart Citations
“…A previous systematic comparison [18] instead found that the use of SAVERX for denoising data and scran for clustering yielded better performance on the ability to recover differentially expressed genes, whereas we focused on the ability to recover cell populations. Another disagreement with the present recommendations come from the study of Hou et al [10] that recommends SAVERX and discourage the use of DCA for better clustering, whereas our study found opposite results for these tools. Several differences in the design of our study could explain this contrast, such as the use of different metrics (ARI at true number of clusters, mean precision/ recall), of different datasets (Koh, Kumar, simMix simulations) and the use of different filtering and normalization strategies.…”
Section: Limitations and Open Questionscontrasting
confidence: 99%
“…The performance of scVI in our evaluation was lower than in the original publication presenting the method [38]. Our results are however in line with other studies comparing silhouette score [58] and clustering accuracy [10] of scVI's latent space. These studies, like ours, used datasets with relatively few cells (i.e., fewer than genes), for which scVI was reported by its authors to be less adapted.…”
Section: Limitations and Open Questionssupporting
confidence: 88%
See 1 more Smart Citation
“…A previous systematic compar- 411 ison [18] instead found that the use of SAVERX for denoising data and scran for clustering yielded 412 better performance on the ability to recover differentially-expressed genes, whereas we focused on 413 the ability to recover cell populations. Another disagreement with the present recommendations 414 come from the study of Hou et al [10] that recommends SAVERX and discourage the use of DCA 415 for better clustering, whereas our study found opposite results for these tools. Several differences 416 in the design of our study could explain this contrast, such as the use of different metrics (ARI 417 at true number of clusters, mean precision/ recall), of different datasets (Koh, Kumar, simMix 418 simulations) and the use of different filtering and normalization strategies.…”
contrasting
confidence: 87%
“…The evaluation framework, pipeComp, has 8 been implemented so as to easily integrate any other step or tool, allowing extensible benchmarks 9 and easy application to other fields (https://github.com/plger/pipeComp). 10 Background 11 Single-cell RNA-sequencing (scRNAseq) and the set of attached analysis methods are evolving 12 fast, with more than 560 software tools available to the community [1] , roughly half of which are 13 dedicated to tasks related to data processing such as clustering, ordering, dimension reduction 14 or normalization. This increase in the number of available tools follows the development of new 15 sequencing technologies and the growing number of reported cells, genes and cell populations [2] .…”
mentioning
confidence: 99%